1988
DOI: 10.1029/jd093id01p00759
|View full text |Cite
|
Sign up to set email alerts
|

Trace gas transport in the vicinity of frontal convective clouds

Abstract: Airborne measurements of NOx, NOy, CO, and O3 were conducted in the vicinity of a line of towering cumulus and cumulonimbus clouds (approximate altitude, 9 km) in south‐central Oklahoma, on the afternoon of June 17, 1985. NOx, NOy, and CO concentrations in the upper tropospheric outflow region of these clouds were near environmental levels. Meteorological analyses show that these clouds were located above a cold front, which prevented the entry of air from the boundary layer directly below and near the cloud. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 21 publications
0
45
0
1
Order By: Relevance
“…In the last two decades, some observational campaigns have been conducted worldwide to better understand the role of deep convection and its efficiency to transport gaseous species from the boundary layer to the upper troposphere (UT). Many studies over midlatitudes (Dickerson et al, 1987;Hauf et al, 1995;Pickering et al, 1988) showed that deep convection could pump low tropospheric air to the tropopause region and proved effective transport of trace gases (e.g. CO, O 3 ; Ström et al, 1999;Fischer et al, 2003) even highly reactive and short-lived (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, some observational campaigns have been conducted worldwide to better understand the role of deep convection and its efficiency to transport gaseous species from the boundary layer to the upper troposphere (UT). Many studies over midlatitudes (Dickerson et al, 1987;Hauf et al, 1995;Pickering et al, 1988) showed that deep convection could pump low tropospheric air to the tropopause region and proved effective transport of trace gases (e.g. CO, O 3 ; Ström et al, 1999;Fischer et al, 2003) even highly reactive and short-lived (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The most efficient method for transporting heat, moisture, and chemical tracers from the boundary layer to the upper troposphere and lower stratosphere is through moist convection (e.g., Dickerson, 1987;Pickering et al, 1988;Mullendore et al, 2005) . Deep convection allows constituents from the boundary layer to be transported within tens of minutes into the upper troposphere and lower stratosphere, where longer chemical residence times can increase their impact on the radiative budget, and higher wind speeds can increase their influence region from local to regional or even global (e.g., Dickerson, 1987;Pickering et al, 1993;Thompson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Large scale mixing of pollution throughout the troposphere is accomplished by frontal activity (e.g. Bethan et al, 1998;Fischer et al, 2002) and deep convection, a particularly efficient process for fast Correspondence to: H. Fischer (hofi@mpch-mainz.mpg.de) transport of boundary layer air into the upper troposphere (Dickerson et al, 1987;Pickering et al, 1988;Hauf et al, 1995;Ström et al, 1999). Tropospheric air enters the stratosphere predominantely in the tropics as part of the large scale Brewer-Dobson-circulation (Holton et al, 1995), with a small contribution from deep convection penetrating the tropical tropopause (Danielsen, 1982(Danielsen, , 1993.…”
Section: Introductionmentioning
confidence: 99%